Survey of Native VAM Fungi of Sodic Soils of Haryana State - Thapar, H. S.; Uniyal, Kamla; Verma, R. K. (Indian Forester, 1991)
Surveys were conducted on the occurrence of VAM fungi in Sadic soils of three districts of Haryana State. Thirteen Glomus spp. i.e. Glomus aggregatum, G. albidum, G. caledonius. G. etunicatum, G. fasciculatum. G. macrocarpum, G. maculosum, G. microcarpum. G. monosporum, G. mosseae, G. multicaulis, G. reticula tum and Glomus sp., one Scutellospora, Scutellospora nigra and two species of Sclerocystis. S coremioides and S. sinuosa were isolated and identified. Glomus spp. were most abundant in study sites. Scutellospora was rare and Sclerocystis spp. were frequent. Glomus macrocarpum, Glomus microcarpum and Glomus fasciculatum were isolated in moderate the high frequencies from all the locations. The presence of Glomus albidum, G. maculosum and Scutellospora nigra is reported for the first time from Sodic soils of Haryana State.